THE USE OF INTERPERSONAL INTELLIGENCESTRATEGY TO IMPROVE STUDENTS’ WRITING ABILITY AT THE EIGHT GRADE STUDENT OF SMP SWASTA TAMAN ASUHAN PEMATANGSIANTAR IN ACADEMIC YEAR 2019/2020 - Tiodora Fermiska Silalahi; Rohdearni Wati Sipayung (Program Studi Pendidikan Bahasa Inggris FKIP, 2020)
This experimental study aimed to find out the improving of Context Clues Strategy on Reading Descriptive Text Comprehension. This research was used one group pre-test and post-test design. The reason for conducted this research because students’ tend to used dictionary when they read English text in order to find the meaning of difficult word. However, they may not use dictionary or somes stuff then can help them to understand English text in joining examination. This condition makes students’ difficult to comprehend the English text because they faced different context. So, students should know about reading strategy to increase the reading comprehension without using dictionary or another instrument. One of the appropriate reading strategies to increase the students’ reading comprehension descriptive text ability is context clues. The sample of this research was the seven grade students’ especially class VII/D at SMP NEGERI 1 SIDAMANIK. The participants were 34 students. The step of research procedure are conducting pre-test, treatment, post-test and data analysis. The data analysis by using table categories. The data analysis showed there is significant improving of using Context Clues Strategy on reading descriptive text comprehension. The finding also proved that in the pre-test students mean score was only 39.11 and post-test score was improved to 71.11 and standard deviation of pre-test score was only 6.78 and post-test score was 12.08